Pengaruh Kualitas Produk Dan Lokasi Terhadap Keputusan Pembelian Kopi Di Kedai Kopi Sachi Surabaya - M Ivan AlFaris; Handy Aribowo; Achmad Djoni Sudirman (Journal of Creative Power and Ambition (JCPA), 2024)
The decision to purchase coffee at the Sachi coffee shop is not completely optimal, which can be seen from the fluctuating income of the Sachi Coffee Shop. This is caused by the suboptimal product quality, location and consumer motivation in making purchases at Kedai Kopi Sachi. This research aims to determine the influence of product quality, location and consumer motivation variables on coffee purchasing decisions at Sachi Coffee Shop. The data used in this research is primary data obtained by distributing questionnaires to process data regarding purchasing decisions, product quality, location and consumer motivation. Secondary data is obtained from literature, books, scientific journals, theses and other data sources related to research. This research uses quantitative methods. The independent variables used in this research are product quality (X1), location (X2). Based on the results of the T test, the product quality variable (X1) has a regression coefficient value of 0.19, indicating that tcount (2.353) > ttable (1.984) has a positive and significant effect. Location (X2) has a positive and significant effect on the decision to purchase coffee at the Sachi Coffee Shop in Surabaya. The regression coefficient value of (0.222) shows that tcount (3.465) > ttable (1.984) has a positive and significant effect. Based on the results of the F test, all independent variables have a close influence and have significance on the dependent variable, namely purchasing decisions (Y). The results of the F test research obtained a value of f count 21.278 > f table 3.090 with a significance level of 0.000 < 0.05, so it can be concluded that the quality variable product and location simultaneously influence the coffee purchasing decision variable at the Sachi Coffee Shop in Surabaya.